A high‐resolution genomic analysis of multidrug‐resistant hospital outbreaks of Klebsiella pneumoniae. Issue 3 (20th February 2015) - Chung The, Hao; Karkey, Abhilasha; Pham Thanh, Duy; Boinett, Christine J; Cain, Amy K; Ellington, Matthew; Baker, Kate S; Dongol, Sabina; Thompson, Corinne; Harris, Simon R; Jombart, Thibaut; Le Thi Phuong, Tu; et al.
Abstract Multidrug‐resistant (MDR) Klebsiella pneumoniae has become a leading cause of nosocomial infections worldwide. Despite its prominence, little is known about the genetic diversity of K. pneumoniae in resource‐poor hospital settings. Through whole‐genome sequencing (WGS), we reconstructed an outbreak of MDR K. pneumoniae occurring on high‐dependency wards in a hospital in Kathmandu during 2012 with a case‐fatality rate of 75%. The WGS analysis permitted the identification of two MDR K. pneumoniae lineages causing distinct outbreaks within the complex endemic K. pneumoniae. Using phylogenetic reconstruction and lineage‐specific PCR, our data predicted a scenario in which K. pneumoniae, circulating for 6 months before the outbreak, underwent a series of ward‐specific clonal expansions after the acquisition of genes facilitating virulence and MDR. We suggest that the early detection of a specific NDM‐1 containing lineage in 2011 would have alerted the high‐dependency ward staff to intervene. We argue that some form of real‐time genetic characterisation, alongside clade‐specific PCR during an outbreak, should be factored into future healthcare infection control practices in both high‐ and low‐income settings.